Modifiable risk factors for scald injury in children under 5 years of age: a multi-centre case–control study - Stewart, Jane; Benford, Penny; Wynn, Persephone; Watson, Craig M; Coupland, Carol; Deave, Toity; Hindmarch, Paul; Majsak-Newman, Gosia; Kendrick, Denise (Elsevier, 2016)
Objective: To determine the relationship between a range of modifiable risk factors and medically attended scalds in children under the age of 5 years. Methods: Multicentre matched case-control study in acute hospitals, minor injury units and GP practices in four study centres in England. Cases comprised 338 children under 5 presenting with a scald, and 1438 control participants matched on age, sex, date of event and study centre. Parents/caregivers completed questionnaires on safety practices, safety equipment use, home hazards and potential confounders. Odds ratios were estimated using conditional logistic regression. Results: Parents of cases were significantly more likely than parents of controls to have left hot drinks within reach of their child (adjusted odds ratio (AOR) 2.33, 95%CI 1.63, 3.31; population attributable fraction (PAF) 31%). They were more likely not to have taught children rules about climbing on kitchen objects (AOR 1.66, 95%CI 1.12, 2.47; PAF 20%); what to do or not do when parents are cooking (AOR 1.95, 95%CI 1.33, 2.85; PAF 26%); and about hot things in the kitchen (AOR 1.89, 95%CI 1.30, 2.75; PAF 26%). Conclusions: Some scald injuries may be prevented by parents keeping hot drinks out of reach of children and by teaching children rules about not climbing on objects in the kitchen, what to do or not do whilst parents are cooking using the top of the cooker and about hot objects in the kitchen. Further studies, providing a more sophisticated exploration of the immediate antecedents of scalds are required to quantify associations between other hazards and behaviours and scalds in young children.